Delayed complication of radiotherapy: Laryngeal fibrosis and bilateral vocal cord immobility - Prepageran, Narayanan; Rajagopalan, Raman (Malaysian Medical Association, 2005)
Radiotherapy is the accepted treatment for early laryngeal carcinomas with the advantage of voice preservation. It is however, not without complications. We report a case of bilateral vocal cord immobility 15 years after radiotherapy. This appears to be due to ankylosis of cricoarytenoid joint and fibrosis of the larynx.